Educating new graduate nurses in their first year of practice: The perspective and experiences of the new graduate nurses and the director of nursing. (May 2018) - Doughty, Lesley; McKillop, Ann; Dixon, Robyn; Sinnema, Claire
Abstract: New graduate nurses are the future of nursing and the education they receive as they transition into the workforce as a newly registered nurse is critical for building a suitably qualified nursing workforce that will adequately serve the future population. Variation exists in education programmes for new graduate nurses in their first year of practice which is known to impact on transition experience. A qualitative study using focus groups and semi-structured interviews was undertaken to explore the experiences and perceptions of New Graduate Nurses undertaking a new graduate programme and Directors of Nursing supporting them to complete the programme which may or may not have been inclusive of a postgraduate course (Masters Level). The findings of this study are in line with previous research and support the value of new graduate programmes but did reveal a lack of consensus in regards to the structure and content of such programmes. This study revealed some commonalities and challenges between the differing programmes but has identified the need for further research to establish the impact of postgraduate education in the first year of practice and how this impacts on nursing practice and patient care. There are numerous terms in the literature with reference to new graduate programmes; transition to practice programme, nurse entry to practice programme, first year of clinical practice programme, new graduate programme and early career nursing programme. For the purpose of this article the term Nurse Entry to Practice (NETP) will be used in reference to any form of new graduate programme. Highlights: The findings of this study reveal a lack of consensus around the structure and content of new graduate programmes. Further research should address this issue and also examine if the inclusion of a PG Course results in better patient outcomes. This study is the first to have considered experiences and perceptions of NGs and DONs relating to new graduate programmes. Some benefits and challenges have been revealed identifying a need for further research to establish the impact of NG programmes on patient outcomes.